Implementasi Model View Controller Dengan framework CodeIgniter Pada Perpustakaan - Ardian Dwi Praba (Universitas Bina Sarana Informatika, 2018)
Abstract - in this era of disruptive like nowadays, information systems are becoming staples in every area that we do. Almost all jobs have an information system that is used to help complete the work so that it becomes more effective. Library processing a lot of data that should be processed well and fast that can give you maximum service to our customers. Besides information system built to manage all data, the security of information systems should be a major concern so that data can be stored safely and avoid attack or deface from people who are not responsible. One way to secure information systems we make is by separating the model view and the controller so that the system will be difficult to hack or on disable. With the CodeIgniter Framework then we would be easier in making a website that is secure because in the CodeIgniter has the concept of the Model View Controller (MVC). Keywords: Framework, CodeIgniter, Sistem, mvc